Faktor-Faktor Yang Mempengaruhi Firm Value Pada Perusahaan Manufaktur - Cindy Lesmana, Tony Sudirgo (Jurnal Paradigma Akuntansi, 2019)
This study aimed at finding out whether the factors such as profitability, firm size, liquidity, and sales growth influenced firm value on manufacturing companies listed in Indonesian Stock Exchange, especially during 2015-2017. The sampling method used purposive sampling with total sample of 93 datas which is financial statement from www.idx.co.id. The collected datas were analyzed using statistic descriptive, likelihood/ chow test, hausman test, and hypothesis test by using Eviews 9.0. The research results indicate that independent variables explained the dependent variable up to 95,9779%, while the remaining 4,1221% explained by other factors. Firm size affected firm value, while profitability, liquidity, and sales growth did not affect firm value